Performance of corrosion inhibitors in reinforced concrete elements under electrical voltage. (1st August 2022) - Lapiro, Igor; Mezhov, Alexander; Kovler, Konstantin
Highlights: Inhibitors based on potassium fluorosilicate and amine carboxylate showed the best resistance to stray current over others. Beyond 3.6 V electrical potential, the higher the concrete strength, the more efficient is the corrosion inhibition. There are five phases in corrosion kinetics that represent the change in electrical resistance of a reinforced concrete sample: Corrosion onset; Corrosion filling phase; Crack formation; Crack growth and construction failure. The benefits of corrosion inhibitors have no significant effect when a crack corresponding to the margins is created. Abstract: The current paper develops a novel accelerated corrosion test method based on Faraday's law to investigate the performance of different inhibitors in reinforced concrete elements under electrical voltage. Using the proposed method two commercially available and three lab-made inhibitors were tested. Lab-made inhibitors based on potassium fluorosilicate and amine carboxylate showed the best performance over others. Furthermore, it is found that under an electrical potential environment beyond 3.6 V, the higher the concrete strength, the more efficient is the corrosion inhibition. Based on experimental results, a novel model describing the corrosion evolution in reinforced concrete was proposed.